The body in history, culture, and the arts
1 online resource.
Keywords: "The aim of this book is to explore the body in various historical contexts and to take it as a point of departure for broader historiographical projects. The chapters in the volume present the ways in which the body constitutes a valuable and productive object of historical analysis, especially as a lens through which to trace histories of social, political, and cultural phenomena and processes. More specifically, the authors use the body as a tool for critical re-examination of particular histories of human experience, and of societal and cultural practices, thus contributing to the burgeoning area of body history in terms of both specific case studies as well as historiography in general"--